A formação de professores alfabetizadores dentro do Pacto Nacional pela Alfabetização na Idade Certa (2012-2013): propostas, desenvolvimento e repercussões na prática docente - Messora, Gisele Pedroso de Almeida (2018)
The aim of this research is the PNAIC graduation course of literacy teachers, which took place in Osasco city in 2013. The general objective is to understand how the course proposal and didactics are present in two graduated teacher´s pedagogical practice and professional constitution. The specific objectives would be: 1) Generate records about the course, by collecting, organizing information and modus operandi description; 2) Analyze the course according to the bibliography considered in this paper, by emphasizing its connection with municipal, state, national and international policies of literacy promotion and teacher´s continued formation; 3) Present the portfolio of two teachers in formation, as instruments of their own formation process. 4) Analyze in the portfolio the elements that were produced and its close relation with the course proposal (directives and objectives), by illustrating how each pedagogue has appropriated of the course contents; and 5) Elaborate and understand the impacts in two pedagogues in formation, by analyzing the content and elements of the semi structured interviews. It was taken the assumption that it is possible to verify by portfolio and interview content analysis, the pedagogue formation proposal effectiveness present in National Pact for Literacy in the Right Age (PNAIC), in pedagogic practice and teacher's professionalism. This research of qualitative intent will be constituted mainly of three methodological procedures: (1) theoretical and document study, (2) portfolio analysis and (3) open questionnaire.